2002
DOI: 10.1111/j.1755-6724.2002.tb00095.x
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of the Gas Hydrate Stability Zone in the South China Sea

Abstract: Based on the analysis of sea‐bottom temperature and geothermal gradient, and by means of the phase boundary curve of gas hydrate and the sea‐bottom temperature versus water depth curve in the South China Sea, this paper studies the temperature and pressure conditions for gas hydrate to keep stable. In a marine environment, methane hydrate keeps stable at water depths greater than 550 m in the South China Sea. Further, the thickness of the gas hydrate stability zone in the South China Sea was calculated by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The marine sediments [24][25][26] cover a wide range of water depth, from about 470 m to 3000 m corresponding to the pressure from 4.7 MPa to 30 MPa and the range of temperature from 2.2 to 10 • C [27]. Microbial metabolism was extremely slow if the temperature below 4 • C. Previous experiment studies showed that when the temperature was higher than 4 • C, the metabolism of anaerobic microbes accelerated, and authigenic minerals are easier to form [19].…”
Section: Methodsmentioning
confidence: 99%
“…The marine sediments [24][25][26] cover a wide range of water depth, from about 470 m to 3000 m corresponding to the pressure from 4.7 MPa to 30 MPa and the range of temperature from 2.2 to 10 • C [27]. Microbial metabolism was extremely slow if the temperature below 4 • C. Previous experiment studies showed that when the temperature was higher than 4 • C, the metabolism of anaerobic microbes accelerated, and authigenic minerals are easier to form [19].…”
Section: Methodsmentioning
confidence: 99%
“…Ds is the diffusion coefficient of the whole sediment package after curve correction, C is the concentration of components in pore water, x is depth, and dc/dx is the vertical concentration gradient. This study assumed that the average pH value of sediment for all research stations was 7.5, and the bottom water temperature was uniformly set as 5 °C (refer to (Jin and Wang, 2010). The diffusion coefficients D SW (m 2 s -1 ) of pore water components (SO 4 2-, CH 4 , Ca 2+ , DIC) at the relevant temperature and salinity were taken from Schulz (2006) and corrected for the set temperature and salinity.…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Now, these gas sources are still in the major gas generating and accumulation stages. Rapid sedimentation and strong thermotectonic movements since the Neogene not only accelerate the generation of natural gas in this region, but also promote coexistence of hydrocarbon gas, N2 and COZ formed in different stages (from a shallow diagenetic stage: R,,<0.50% to a para-metamorphic stage at deptb: R 2 3 8 ) (Jin and Wang, 2002). This resulted in the reservoiring history of complex composition and multi-phase gas migration and accumulation in the Yinggehai Basin, and also resulted in the evident difference in composition and properties of the natural gas in different gas-bearing formations in the same gas field ( Fig.…”
Section: Basinmentioning
confidence: 99%